Quick-gelation dual-network hydrogel as well as preparation method and application thereof
By mixing MXene with substances such as chitosan and acrylamide at room temperature, and adding metal ionic salts and initiators, a dual network hydrogel is quickly formed, which solves the problems of long gelation time and large energy dissipation of existing hydrogels, and achieves high viscosity, conductivity and low energy dissipation of hydrogels, suitable for wearable sensors.
Patent Information
- Application Number
- CN202311335607.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-16
AI Technical Summary
The gelation process of existing hydrogels usually requires specific conditions, such as light or heating, and the gelation time is long and the energy dissipation is large, making it difficult to quickly synthesize hydrogels with high viscosity, conductivity and low energy dissipation at room temperature.
By mixing the aqueous solution of MXene with chitosan acetic acid solution and acrylamide and other substances under normal temperature, and adding metal ion salts and initiators, the reduction activity of MXene and the redox reaction of the initiator can be used to quickly form a dual network hydrogel.
It achieves rapid gelation within 5-15 seconds at room temperature, with high tensile properties, wide strain detection range, low energy dissipation and excellent adhesion, and is suitable for wearable sensor applications.
Smart Images

Figure CN119842012A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogels, in particular to a fast-gelling double-network hydrogel and a preparation method and application thereof. Background Art
[0002] In recent years, wearable devices have become increasingly common in our daily lives, from smart watches that can track body temperature, steps, and heart rate, to various forms of wearable devices such as tattoos and textiles. Wearable devices have important commercial value in numerous applications. Hydrogels have gradually gained attention and developed rapidly due to their biocompatibility, stretchability, adhesion and other properties. However, in the process of studying hydrogels, people have noticed that the gelation process usually requires specific conditions such as light and heating. For example, polyvinyl alcohol (PVA) hydrogels require multiple freeze-thaw cycles in a liquid nitrogen environment to establish hydrogen bonds and form a gel structure, while polyacrylamide (PAA) hydrogels need to decompose free radicals at high temperatures to form a continuous polymer network. These gelation processes are not only time-consuming, but may also lead to problems such as incomplete reactions and insufficient performance in actual environments. Therefore, there is an increasing need to develop and study hydrogels with rapid gelation capabilities.
[0003] Yuxi Li et al. (Reference - ACS Nano 2022, 16, 1567-1577) controlled Fe 3+ MXene-polyacrylic acid (PAA)Fe prepared by infiltration 3+ Multi-bond network physical hydrogel can obtain MXene-PAA hydrogel within ten minutes at room temperature. However, the hydrogel has obvious energy dissipation during the stretching process, and the energy dissipation coefficient of the first circle reaches 0.7. Therefore, how to combine fast and low-cost preparation with high viscosity, conductivity, and low energy dissipation to prepare a multifunctional hydrogel is a very challenging task. Summary of the invention
[0004] The invention provides a fast-gelling double-network hydrogel and a preparation method and application thereof. Under normal temperature conditions, the hydrogel can be quickly synthesized without any form of energy initiation.
[0005] The technical solution of the present invention is achieved as follows: a method for preparing a fast-gelling double-network hydrogel comprises the following steps:
[0006] (1) Adding the aqueous solution of MXene to the acetic acid solution of chitosan and ultrasonically dispersing it;
[0007] (2) then adding and dissolving aqueous solutions of metal ion salt, acrylamide (AAM) and NN-methylenebisacrylamide (MBAA);
[0008] (3) Finally, an initiator is added to form a double network hydrogel under room temperature conditions.
[0009] Chitosan is dispersed in the aqueous solution in the form of polymer chains, and acrylamide is dispersed in the form of short chains. When the initiator is added, the short acrylamide chains form long chains through the cross-linking agent NN-methylenebisacrylamide, thus synthesizing a double network hydrogel.
[0010] When MXene is added to the synthesis system of hydrogel, the Ti 2p orbital spectrum of MXene nanosheets shows that the Ti 2+ and Ti 3+ The characteristic peaks show that MXene nanosheets have strong reduction activity and undergo redox reactions with initiators, thereby reducing the decomposition activation energy of the initiator, generating a large number of free radicals, and leading to the rapid gelation phenomenon. At the same time, the addition of MXene nanosheets also improves the conductivity, self-adhesion and stretchability of the hydrogel. First, MXene nanosheets form conductive pathways inside the hydrogel, solving the problem of poor conductivity of the hydrogel due to the fact that it is a polymer. Secondly, various functional groups (-OH, -F, etc.) on the MXene nanosheets can form chain entanglement structures, electrostatic interactions and supramolecular interactions with chitosan chains, and together form an extensible hydrogel network, further improving the self-adhesion and stretchability of the hydrogel, so that the functions of the various parts of the hydrogel can work together to form an integrated wearable monitoring platform.
[0011] Furthermore, the metal ion salt is ferric nitrate.
[0012] Further, the initiator includes 2,2-azobis(2-methylpropylimidazole) dihydrochloride (AIBA) and ammonium persulfate (APS).
[0013] Further, the aqueous solution of MXene contains 5-25 mg of MXene;
[0014] The amount of chitosan acetic acid solution is 15-25 g. The preparation of chitosan acetic acid solution is as follows: 3-5 g chitosan (CS) is dissolved in 200 ml of 0.2 M (mol / L) acetic acid solution;
[0015] The amount of metal ion salt used is 500-1000 mg, the amount of AAM used is 3-5 g, the amount of MBAA aqueous solution used is 350-900 ul, and the concentration of MBAA aqueous solution is 1 wt%;
[0016] The initiator includes 200-600ul of AIBA aqueous solution and 3-5ml of APS aqueous solution. The concentration of APS aqueous solution is 0.7wt%, and the concentration of AIBA aqueous solution is 10wt%.
[0017] Furthermore, in step (3), the gelation time is 5-15 seconds. The gelation time can be 5 seconds, 7 seconds, 10 seconds, 12 seconds, 15 seconds, etc.
[0018] Compared with other reported literature, the hydrogel with a gel time of 5-15s is several orders of magnitude faster than the conventional preparation process, and no energy in the form of heat, light, etc. is required during the preparation process.
[0019] Furthermore, the aqueous solution of MXene is prepared as follows: 2 g Ti3AlC2 powder and 2 g LiF are added to 40 ml of 9 M HCl solution, stirred at 35 °C for 22-34 h, and then the product is washed with deionized water until the pH value of the solution is 7, and the supernatant after washing is collected.
[0020] A fast-gelling double-network hydrogel is prepared by the preparation method.
[0021] A fast-gelling double-network hydrogel comprises a three-dimensional network structure formed by the entanglement of chitosan chains and polyacrylamide chains, wherein the three-dimensional network structure is doped with Mxene nanosheets and metal ions.
[0022] A fast-gelling double-network hydrogel for use in wearable sensors.
[0023] Beneficial effects of the present invention:
[0024] The present invention utilizes the combined action of MXene and metal ions to synthesize a MXene-based conductive hydrogel with rapid gelation ability. This hydrogel gels within 5-15 seconds at room temperature and does not require any induced energy input. At the same time, the double network hydrogel prepared by the present invention has high stretchability (1350%), wide strain detection range (100-500%), high sensitivity (GF=2.86 at 300-500% strain), low energy dissipation (0.40 kJ m at 100% strain), and high sensitivity (GF=2.86 at 300-500% strain). -3 ) and a double network hydrogel with excellent adhesion. This hydrogel can be easily attached to the surface of human skin to monitor large-scale and subtle human movements, showing stability and repeatability, which provides a promising direction for integrated wearable smart devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 The figures are the actual photos of the hydrogels of Example 1 and Comparative Examples 1-2;
[0027] Figure 2 Stress-strain curves of the hydrogels prepared in Examples 1-5 and Comparative Examples 3 and 4;
[0028] Figure 3 PAA-C-Fe-M prepared in Example 1 10 Mechanical property curve of hydrogel;
[0029] Figure 4 PAA-C-Fe-M prepared in Example 1 10 Ten times of stickiness comparison chart.
[0030] Figure 5 PAA-C-Fe-M prepared in Example 1 10 Real-time resistance change of hydrogel monitors the electrical self-healing behavior of hydrogel.
[0031] Figure 6 PAA-C-Fe-M prepared in Example 1 10 Illustration of hydrogel's recognition of different vocalizations. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] A method for preparing a fast-gelling double-network hydrogel comprises the following steps:
[0035] (1) Dissolve 4 g of CS in 200 ml of 0.2 M acetic acid solution and stir for 12 h to dissolve, thereby obtaining an acetic acid solution of chitosan;
[0036] Preparation method of MXene aqueous solution: add 2g Ti3AlC2 powder and 2g LiF into 40ml 9M HCl solution, stir at 35°C for 22-34h, then wash the product with deionized water until the pH value of the solution is 7, collect the supernatant after washing, and filter the obtained supernatant to measure the concentration;
[0037] An aqueous solution containing 10 mg of MXene was added to an acetic acid solution of 20.5 g of chitosan and ultrasonically dispersed at a power of 500 W for 30 minutes. The water content in the aqueous solution of MXene did not affect the preparation of the double network hydrogel, as long as the MXene content was 10 mg.
[0038] (2) Then add 4.6 g of AAM, 500 mg of ferric nitrate, and 390 ul of MBAA aqueous solution and stir for 15 min;
[0039] (3) Finally, 600 μl of AIBA aqueous solution and 3.6 ml of APS aqueous solution were added, and then transferred to the mold and placed for 10 seconds to obtain a fast-gelling double network hydrogel (abbreviated as: PAA-C-Fe-M 10 ). The concentration of MBAA aqueous solution is 1 wt %, the concentration of APS aqueous solution is 0.7 wt %, and the concentration of AIBA aqueous solution is 10 wt %.
[0040] Example 2
[0041] This embodiment is substantially the same as embodiment 1, except that in step (1), an aqueous solution containing 5 mg of MXene is added to an acetic acid solution containing 20.5 g of chitosan to prepare PAA-C-Fe-M5.
[0042] Example 3
[0043] This embodiment is basically the same as embodiment 1, except that: in step (1), an aqueous solution containing 15 mg of MXene is added to an acetic acid solution of 20.5 g of chitosan; PAA-C-Fe-M 15 .
[0044] Example 4
[0045] This embodiment is basically the same as embodiment 1, except that: in step (1), an aqueous solution containing 20 mg of MXene is added to an acetic acid solution of 20.5 g of chitosan; PAA-C-Fe-M 20 .
[0046] Example 5
[0047] This embodiment is basically the same as embodiment 1, except that: in step (1), an aqueous solution containing 25 mg of MXene is added to an acetic acid solution of 20.5 g of chitosan; PAA-C-Fe-M 25 .
[0048] Comparative Example 1
[0049] This comparative example is basically the same as Example 1, except that: in step (1), no MXene aqueous solution is added, and in step (2), 4.6 g of AAM, 500 mg of ferric nitrate, and 390 ul of MBAA aqueous solution are added to 20.5 g of chitosan acetic acid solution.
[0050] Comparative Example 2
[0051] This comparative example is substantially the same as Example 1, except that in step (2), no ferric nitrate is added.
[0052] Figure 1 The following are photos of the hydrogels of Example 1 and Comparative Examples 1-2. Figure 1 It can be seen that the simultaneous introduction of MXene and iron ions is also the basis for the rapid formation of hydrogels. 3+ In the hydrogel of MXene, there is no rapid gelation phenomenon, but after the introduction of both, the hydrogel changes from a flow state to a gel state within 10s.
[0053] Comparative Example 3
[0054] First, 4g CS was dissolved in 200ml 0.2M acetic acid solution and stirred for 12h to dissolve, to obtain chitosan acetic acid solution; 4.6g AAM and 390ul MBAA aqueous solution were added to 20.5g chitosan acetic acid solution and stirred for 15min; then 600ul AIBA aqueous solution and 3.6ml APS aqueous solution were added and stirred for 15min. Finally, the hydrogel was placed in an oven at 80℃ for free radical polymerization for 10min to obtain a hydrogel (abbreviated as: PAA-C).
[0055] Comparative Example 4
[0056] This comparative example is basically the same as Example 1, except that: in step (1), no MXene aqueous solution is added; in step (2), 4.6 g of AAM, 500 mg of ferric nitrate, and 390 ul of MBAA aqueous solution are added to 20.5 g of chitosan acetic acid solution and stirred for 15 min; (3) then 600 ul of AIBA aqueous solution and 3.6 ml of APS aqueous solution are added, stirred for 15 min, and finally placed in an oven at 80°C for free radical polymerization for 10 min to obtain a hydrogel (abbreviated as: PAA-C-Fe).
[0057] Figure 2 The stress-strain curves of the hydrogels prepared in Examples 1-5 and Comparative Examples 3 and 4 are shown in FIG. Figure 2 It can be seen that compared with the hydrogels PAA-C and PAA-C-Fe, PAA-C-Fe-M 10 The strain of the hydrogel can reach 1350%.
[0058] Figure 3 Mechanical property curves of the hydrogel prepared in Example 1, (a) PAA-C-Fe-M 10 Tensile loading-unloading curves of hydrogels in the strain range of 100%-1000%; (b) PAA-C-Fe-M 10 Total energy, dissipated energy, and energy dissipation rate of the hydrogel in the strain range of 100%-1000%; (b) PAA-C-Fe-M 10 100 loading-unloading cycles of the hydrogel at 100% strain; (d) PAA-C-Fe-M 10 Total energy, dissipated energy, and energy retention of the hydrogel during 100 loading-unloading cycles at 100% strain. Figure 3 It can be seen that PAA-C-Fe-M 10 The stress curves of the hydrogel when loaded and unloaded with different strains increased along the previous path, proving that the hydrogel has good elastic recovery ability. It was also found that the hydrogel had only a small energy dissipation (Mullins effect) in a large strain range, and no obvious hysteresis regression line was observed.
[0059] Depend on Figure 3 b shows that as the strain increases, the total energy required increases sharply, but the energy consumed is only 0.40 kJ / m at 100% strain. 3 The lift is 11.34 kJ / m at 1000% strain 3 , the energy loss rate is somewhat reduced under large strain, from 10.76% under 100% strain to 5.80% under 1000% strain. Figure 3c shows that the tensile stress value of the hydrogel decreases slightly within 100 cycles, from 6.4 kPa in the first cycle to 6.3 kPa in the 100th cycle, proving the existence of the Mullins effect. Figure 3 d shows that the hydrogel only experienced a slight energy drop in the first cycle, from 3.80 kJ / m 3 Reduced to 3.64 kJ / m 3 But then the energy stabilized at 3.65kJ / m 3 The energy loss within 100 turns is also 0.36kJ / m 3 Therefore, the hydrogel exhibited a stable energy retention rate of 90% within 100 cycles of loading-unloading cycle experiment.
[0060] Comparison of PAA-C, PAA-C-Fe and PAA-C-Fe-M 10 PAA-C-Fe-M hydrogel has better adhesion to wood boards, cardboards, glass, etc. Figure 4 PAA-C-Fe-M prepared in Example 1 10 Ten times of viscosity comparison chart. Take more than three PAA-C-Fe-M 10 After the hydrogel samples were adhered ten times, the viscosity of the ten times was compared. It was found that even though the hydrogel had some viscosity attenuation in the second use, the viscosity of the hydrogel was very stable in the 2nd to 10th viscosity tests, proving that the hydrogel meets the requirements of multiple uses.
[0061] Compared with the conductivity of PAA-C and PAA-C-Fe of 0.123S / m and 0.139S / m, PAA-C-Fe-M 10 The conductivity of the hydrogel is about 0.265 S / m, which is doubled. 10 The hydrogel (50 mm, 5 mm wide, 3-4 mm thick strip) was fixed at both ends on the fixed and movable clamps of the stretching machine. The length of the hydrogel exposed between the clamps was 30 mm. The stretching speed was 1% / s. The resistance change was measured using the formula The sensitivity GF of the hydrogel was calculated, and it had an excellent and very stable change rate in the large strain range of 100-500%. At the strain of 0-100%, the sensitivity GF = 0.88, and at the strain of 100-300%, the GF increased to 1.655, and at the strain of 300-500%, the GF further increased to 2.86.
[0062] Figure 5 PAA-C-Fe-M prepared in Example 1 10Real-time resistance change of hydrogel monitors the electrical self-healing behavior of hydrogel. Figure 5 It can be seen that PAA-C-Fe-M 10 The hydrogel can complete the recovery of electrical properties within 0.91s, proving that the hydrogel has a certain electrical self-healing ability.
[0063] PAA-C-Fe-M prepared in Example 1 10 The hydrogel self-adhered to the throat, and the slight movements of the throat were monitored for different vocalizations. Figure 6 PAA-C-Fe-M prepared in Example 1 10 The hydrogel's recognition diagrams of different sounds show that different electrical signal changes were detected when the pronunciations were "A", "AB" and "ZZU". The signal waveform was able to remain stable after multiple tests, proving that the hydrogel can stably monitor and identify slight movements.
[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a fast-gelling double-network hydrogel, characterized in that: The following steps are involved: (1) Adding the aqueous solution of MXene to the acetic acid solution of chitosan and ultrasonically dispersing it; (2) then adding and dissolving aqueous solutions of metal ion salts, AAM and MBAA; (3) Finally, an initiator is added to form a double network hydrogel under room temperature conditions.
2. The method for preparing a fast-gelling double-network hydrogel according to claim 1, characterized in that: The metal ion salt is ferric nitrate.
3. The method for preparing a fast-gelling double-network hydrogel according to claim 1 or 2, characterized in that: Initiators include AIBA and ammonium persulfate APS.
4. The method for preparing a fast-gelling double-network hydrogel according to claim 1, characterized in that: The aqueous solution of MXene contains 5-25 mg of MXene; The amount of chitosan acetic acid solution is 15-25 g. The preparation of chitosan acetic acid solution is as follows: 3-5 g chitosan is dissolved in 200 ml of 0.2 M acetic acid solution; The amount of metal ion salt used is 500-1000 mg, the amount of AAM used is 3-5 g, the amount of MBAA aqueous solution used is 350-900 ul, and the concentration of MBAA aqueous solution is 1 wt%; The initiator includes 200-600ul of AIBA aqueous solution and 3-5ml of APS aqueous solution. The concentration of APS aqueous solution is 0.7wt%, and the concentration of AIBA aqueous solution is 10wt%.
5. The method for preparing a fast-gelling double-network hydrogel according to claim 1 or 4, characterized in that: In step (3), the gelation time is 5-15 s.
6. The method for preparing a fast-gelling double-network hydrogel according to claim 1 or 4, characterized in that: The preparation method of MXene aqueous solution is as follows: add 2g Ti3AlC2 powder and 2g LiF to 40ml 9M HCl solution, stir at 35°C for 22-34h, then wash the product with deionized water until the pH value of the solution is 7, and collect the supernatant after washing.
7. A fast-gelling double-network hydrogel prepared by the preparation method according to any one of claims 1 to 6.
8. The double network hydrogel according to claim 7, characterized in that: The invention comprises a three-dimensional network structure formed by the entanglement between chitosan chains and polyacrylamide chains, wherein the three-dimensional network structure is doped with Mxene nanosheets and metal ions.
9. Use of the double network hydrogel according to claim 7 or 8 in a wearable sensor.
Citation Information
Patent Citations
High-strength, anti-freezing and conductive chitosan / acrylamide dual-network hydrogel and preparation method thereof
CN109134762A
MXene hydrogel with high strength, electrical conductivity and high and low temperature resistance, and preparation method and application thereof
CN110922611A
Hydrogel capable of rapidly gelling as well as preparation method and application of hydrogel
CN114163665A
MXene high-strength composite hydrogel as well as preparation method and application thereof
CN114426682A
Wide-temperature tough conductive composite hydrogel as well as preparation method and application thereof
CN114805858A